Law and Regulation of Air Cargo - Abeyratne, Ruwantissa (Springer International Publishing, 2018)
This book explores the legal and regulatory aspects of the complex air cargo sector, discussing in detail the general principles of the carriage of air cargo; artificial intelligence and air cargo; facilitation; carriage of hazardous goods; human remains; and animals, as well as cargo security; price fixing and anti competitive conduct in air cargo operations; liability issues; the air cargo supply chain and contract of carriage. It also discusses related achievements of the International Civil Aviation Organization; the International Air Transport Association and Airports Council International. The value of goods carried by airlines represents 7.4% of the global Gross Domestic Product. While cargo carried by air accounts for less than 1% of global cargo carriage, airlines carry 35% of the value of world trade, making this industry highly valuable and efficient, and the most reliable way to transport goods throughout the world. On average, airlines transport 52 million metric tons of goods per annum, worth an equivalent of $6.8 trillion, i.e. $18.6 billion worth of goods daily. .